Antihyperglycemic and Antihyperlipidemic Effects of Newly Synthesized Glibenclamide Analogues on Streptozotocin-diabetic Rats - Ahmadi, A.; Khalili, M.; Farsadrooh, M.; Ghiasi, M.; Nahri-Niknafs, B. (Drug Research, 2013)
In this study, new glibenclamide analogues (5a–d) with substituted pharmacological triethoxysilyl propan, allyl and ethoxyphenyl groups for cyclohexyl moiety have been synthesized by condensing sulfonamide (4) with related isocyanate or isothiocyanate’s compounds. The newly synthesized drugs were evaluated for their antihyperglycemic and antihyperlipidemic activities with streptozotocin (STZ)-induced diabetic rats. All showed hypoglycemic and hypolipidemic activities compared to the control animals but 5c and 5d exhibited more and significant lowering blood activities similar to glibenclamide. This was concerned with identical affinities to bind with SUR1 receptor. Moreover, the new drugs displayed high efficiency for reducing serum LDL level which resulted in a high HDL/LDL ratio as a good lipid profile compared to other groups.
Keywords: glibenclamide; sulfonylurea; antihyperglycemic; antihyperlipidemic activities